New dispersive IDT (brief note) - DANICKI, E. (Archives of Acoustics, 1994)
A new structure of interdigitaI transducer (IDT) of surface acoustic waves is proposed having useful property as concern the overtone frequency response. The proposed transducer utilizes both dispersive aperiodic system of electrodes, and apodization.